Evaluation Succes Of Program Artificial Insemination On Local Cattle Female In Kuala District Sumatera Utara Province - Isra Miradja (Fakultas Pertanian, Universitas Syiah Kuala, 2023)
The purpose of this study was to analyze the success of the artificial insemination (AI) program in local cattle in Kuala District, Langkat, Sumatera Utara Province. It was conducted in five villages: Bekiung, Beruam, Blankahan, Lau Kersik dan Raja Tengah. The survey method was employed in this study. The respondents were selected by using purposive sampling method. There were 41 breeders and 3 inseminators included as the respondents. To be involved in the study, the breeders had to meet certain criteria, such as having an experience of breeding local cows, at least twice using the AI system. As for the inseminators, they were required to have a permit from the Langkat Livestock Service. The results showed that the conception rate (CR) was 71.88%; the service per conception (S/C) was 1.2; the calving interval (CI) was 12.6 months, and the calving rate (CvR) was 96,66%. This study concluded that the implementation of the artificial insemination program in Kuala, Langkat, has been running effectively.